Composite brake rotor: energy savings and wear performance - Maleque, Md. Abdul (2015)
The global demand for light weight energy savings and high-performance characteristic material has translated to the emergence of advanced composite materials. Presently, cast iron is used for brake rotor production, however, it has very high-density property which makes the brake disc heavier resulting to more fuel consumption and emission of carbon monoxide (CO) thereby making the environment unsafe. The manufacturing process emits harmful amount of CO2 gas during production. The recyclability of the cast iron is advantageous but the evolution of CO2 during remelting has to be taken into consideration. In this invention, lightweight composite brake rotor is fabricated using a modified stir casting method in order to investigate the energy savings potential and also optimize the wear performance of the aluminium matrix composite (AMC) material integrity. This invention is specifically targeted at the automotive industry for automotive brake rotor application. The aim is to develop an energy saving aluminium composite brake rotor with weight reduction and energy savings in order to replace the existing cast iron material brake rotor without sacrificing wear performance. The new composite brake rotor achieved a 50% weight reduction and a corresponding energy savings of 19% when compared to the existing cast iron brake rotor. Moreover, the wear performance AMC exhibited better lubrication contact which in turn improves the life span of the product